Bees Out of the Pandora's Box: Economic Consequences of National Register in Assam. Issue 2 (December 2021) - Sengupta, Atanu; De, Sanjoy
In India, at present, there is a lot of hue and cry for and against the National Register of Citizens (NRC) in Assam. All the arguments are however based on false perception of migration and its ill or well effects on the economy. The latest 2011 Census does not provide the migration tables in detail. Hence, we had no other option but to use theCensus 2001 data to understand the nature and trend of migration in Assam. Our analysis suggests that the recent uproar over illegal migrants from neighboring country in Assam is more of a myth than reality and does not hold much economic justification. Firstly, official data suggests that the flow of internal migration in various districts of Assam is miniscule. Moreover, it is showing a declining trend over the last few decades. The historical international migration that took place in Assam was due to mainly 'push' factor and no such 'push' factors have been in sight in the last few decades. Secondly and more importantly, migration of any form (though waning in Assam) adds to the prosperity and well-being of the state. JEL: J61, J6, Q56